Implementasi Pembelajaran Qira’at Sab’ah Di Pondok Pesantren Nurul Qur’an Bendungrejo Jogoroto Jombang - Khumairoh An Nahdliyah; Nurul Chofifah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2022)
This study aims to describe the implementation sab'ah boarding school in Bendungrejo Jogoroto Jombang, what are the supporting and inhibiting factors in learning qira'ah sab'ah at the Nurul Qur'an Islamic boarding school. So the purpose of this research is to know the learning of qira'at sab'ah in PPNQ, as well as the supporting and inhibiting factors. This study uses a type of field research (field research)and uses a descriptive qualitative approach, the data collection techniques used are observation, interviews and documentation. For data analysis techniques, researchers use data reduction (explaining data), display (presenting data), data drawing (drawing conclusions). As a test of the validity of the data, researchers used triangulation, namely checking data from various sources, methods, and times. The results of the study stated that: Learning qira'at sab'ah at the Nurul Qur'an Islamic Boarding School is taught in three stages, namely: al-mufradat (read per narrator), jama' sughra (read per priest with two narrators) and plural kubra (read combining all priests).The method used is the sorogan and muhafadhah methods, the reference book used is the book of faidl al-baarakat fi sab'il qira'at the work of Al-Maghfirullah KH. M. Arwani AminKudus. The supporting factor is the motivation of the students who are still enthusiastic about participating in qira'at sab'ahlearning, learning through a three-stage process, applying the sorogan method which is student-centric. While the inhibiting factor is the lack of enthusiasm on the part of the students, not all students are able to read the book, with the sorogan method, the students are required to study and understand the contents of the reference book themselves, and there is no evaluation.